A Novel Approach for Transformation of Relational Database into Column-Oriented Database (HBase) - Kaur, Baljit (My University, 2014)
Relational databases have been serving as a storage platform from several decades. However, with the increase in Science and Technology, we are awashed with data. In order to increase scalability and computational power, applications running on existing databases needs to be migrated. Many enterprises are shifting their data from Relational databases towards the databases that provide high availability, flexibility and scalability. Such databases come under category of NoSQL databases. NoSQL databases are open source, non relational Internet age databases. NoSQL data stores are schema-less in nature. In this report, an algorithm has been proposed that approaches towards migration of schema as well as data from Relational database to HBase. HBase is one of the NoSQL database which uses Column Oriented approach. HBase deals with structured as well as unstructured data, providing faster access to random read/write. The proposed algorithm performs schema transformation from MySQL database to HBase and subsequently migrates the data. The algorithm has been well demonstrated with sample database of BIRT.
ME, CSED
Keywords: HBase, Column Oriented Databases, MySQL